Sosialisasi Pemberdayaan Ekonomi Petani Dengan Metode Kerjasama Yang Menguntungkan - Adia Adi Prabowo; Irfan Adi Nugroho; M. Afif Shulhan (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Empowerment of Farming Communities in Enhancing Rural Economic Development. This socialization aims to find out the extent of the role of Farmer Groups in increasing the empowerment of the farming community of Kulwaru Village, Wates District, Kulon Progo Regency and to know the Rights and Obligations of Owners and Cultivators.The main problem of the target audience is to find out how the behavior of the farmers in Kulwaru Village regarding financing and management and calculating the profits of rice farmers. As well as knowing how accounting and local wisdom in the profit-sharing system between the owner rice farmer and the cultivating rice farmer under the guise method. Based on the research, the results obtained from analyzing the results of experience and interviews with rice farmers in Kulwaru Village, Wates District, Kulon Progo Regency produced a form or model of profit sharing cooperation with the